The other side of the coin: When younger workers are discriminated against - Schmitz, S.; Vauclair, C.-M.; Rosa, M.; Patient, D. (International Society for Justice Research 18th biennial conference (ISJR 2021), 2021)
Ageism (age-based discrimination) is the most prevalent form of discrimination, yet still under-researched. Most ageism research focuses on discrimination against older workers, in spite of the fact that individuals can often be judged also as too young. In order to fully understand the role ageism plays in organizations, a better understanding of ageism against younger workers is required. Building on research examining prescriptive stereotypes - that is, “should”-based expectations that seek to control what members of a certain social group are to do - two surveys to shed light on prescriptive stereotypes towards younger workers were conducted. Survey 1 (N=69) asked open-ended questions about age-based expectations regarding younger workers and free listed associations, respectively. Survey 2 (N=77) identified prescriptive and descriptive age stereotypes related to both younger and older workers through real-life critical incidents. Preliminary results show that some of the main age-based expectations regarding younger workers relate to lower status, autonomy, being digital native, conformity, maturity, openness for learning, and vitality. Among the words more commonly used to describe younger workers are “inexperienced”, “lazy”, or “energetic”, and “smart”. Regarding situations of age discrimination, 69 valid situations were described, 60% related to older workers and 40% to younger workers. Feelings regarding, reactions to, and results of these situations are identified and discussed. We contribute to the literature in terms of further understanding ageism against younger workers, namely in regard to prescriptive age stereotypes.